Development of portable checking fixture device for automotive quality-confirmation inspection - Bastian Wibar, Momang (2017)
Automotive body panel quality is imperative, particularly in the automotive industry where radically shortened product development cycle time remains a crucial differentiating factor between the best performing companies and the rest of the industry. Automotive body panel checking processes aim to produce higher quality parts, reduce cost, and achieve higher productivity. Checking fixtures design is required in the automotive parts manufacturing, specifically to check the accuracy of the produced part according to the standard design and reduce the human error by incorporating computer programming. The primary objectives of this thesis were to develop a Portable Checking Fixture Device (PCFD) in order to check the surface accuracy for automotive stamping parts, analyse the surface accuracy of the automotive stamping parts and validate the system of PCFD. The development of a PCFD starts from the design of the gantry system, hardware and software part until the validation of the data. Gantry system Design Four is selected and fabricated according to this design. Aluminium is selected as the primary material used to fabricate the structural gantry of PCFD. Arduino Mega as microcontroller was responsible for processing movement instructions, controlling stepper motors and controlling the reading of the sensor. Ultrasonic distance sensor is used to calibrate the quality surface of the sample panel, and data are examined using computer software to ensure whether it follows the actual Computer Aided Design (CAD) data. Visual Studio software is used to create the user interface and compare the actual value and setting value for the checking point of sample panel in the quality checking process. Then, the data transferred to the computer to be analysed and discussed. Data from three samples are collected, namely sample A, B, and C with three repeated readings. From the data analysis of sample A, 73.33% of the points are accepted and the remaining 26.67% are rejected and for sample C, about 70.00% of the points are accepted and 30.00% are rejected. This finding shows that sample A and C have higher surface quality because the total percentage of the checking point has accepted more than 70%. From the data of sample B, 63.33% of the points are accepted and the remaining 36.67% are rejected. It can be seen that sample B has a lower surface quality because the total percentage of checking point accepted is lower than 70%. Checking time per point produced when checking the surface of sample panel by using PCFD is better than Coordinate Measuring Machine (CMM) used in the automotive industries which are 6.67 seconds. Also, from the Gage Repeatability and Reproducibility (GR&R) study of the measurement system of a PCFD, it is found that the measurement system is acceptable because the number of distinct categories is more than five and the measurement system variation is under 10%. As a conclusion, the PCFD generates the quality analysis of the surface accuracy for an automotive body part that guides the operation of inspection, and the development of a PCFD can be used as are references and guidelines for the engineers to make the development of CFs.